Undergraduate Student’s Perspectives on Transformative Education and Collaborative Learning at Universitas Timor Indonesia - The, Hery Yanto; Lasi, Febronia (Educational Insights, 2024)
The purpose of this study was to analyze the perspectives of undergraduate students at Universitas Timor Indonesia about the concepts of collaboration and innovation in the field of education. We conducted two focus group talks, each lasting 45 minutes, to collect data. Students had a restricted understanding of collaboration and innovation. After the investigation, participants showed an enhanced comprehension of these principles and exhibited a significant inclination to augment their collaborative endeavors in innovation. Students concur that collaborative effort and innovative thinking are vital for enhancing education in Nusa Tenggara Timur (NTT). Collaborative learning fosters knowledge exchange, skill enhancement, and the exploration of unique learning trajectories. Innovation enhances language acquisition by disrupting traditional learning processes, resulting in novel and effective strategies. Additional inquiry into NTT is necessary because of its unique cultural and linguistic landscape, which presents both challenges and opportunities for educational development. By understanding these local dynamics, educators can tailor their approaches to better meet the diverse needs of students, ultimately fostering a more inclusive and effective learning environment.